THE EFFECT OF USING VIDEO TUTORIAL MEDIA ON STUDENTS’ WRITING SKILL IN WRITING PROCEDURE TEXT AT THE TENTH GRADE OF SMA KAMPUS NOMMENSEN PEMATANGSIANTAR - Eksaulina Simanjuntak; Indah Peronika Siahaan2; Imeliana Saragih; Diana Dian Sari Tampubolon; Dumaris Silalahi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Writing is an essential skill in English learning as it enables students to expressideas, thoughts, and feelings in a clear and meaningful way. However, manystudents still face difficulties in writing procedure texts, particularly ingenerating ideas, organizing steps, and using appropriate grammar andvocabulary. This study aims to examine the effectiveness of using video tutorialmedia on students’ writing skills in procedure text at the tenth grade of SMAKampus Nommensen Pematangsiantar.This research employed a quantitativemethod with a pre-experimental design using one-group pre-test and post-test.The participants consisted of 23 students from class X-1 selected throughpurposive sampling. Data were collected using writing tests and analyzedthrough descriptive statistics and a paired sample t-test. The results showed thatthe students’ mean score increased from 56.5 in the pre-test to 76.9 in the posttest,indicating a significant improvement in their writing performance afterbeing taught using video tutorial media.The findings suggest that video tutorialmedia is effective in improving students’ understanding of text structure,language features, and grammatical accuracy in writing procedure texts. Inaddition, the use of video tutorials enhanced students’ motivation andengagement during the learning process. Therefore, video tutorial media can beconsidered an effective and practical instructional tool to enhance students’writing skills, particularly in learning procedure texts.Keyword : Writing Skill, Procedure Text, Video Tutorial Media, Students Writingng Achievement, English Language Teaching